Pengaruh self-discipline dan komitmen sikap terhadap kepemimpinan situasional dan dampaknya pada kapabilitas pegawai - Mamang Hariyanto (FADZAT: Jurnal Ekonomi Syariah, 2022)
The aims of this study are: 1) To analyze the effect of self-discipline on situational leadership. 2) Analyzing the effect of attitude commitment on situational leadership. 3) Analyzing self-discipline on employee capabilities. 4) Analyzing the effect of attitude commitment on employee capabilities. 5) Analyzing the influence of situational leadership on employee capabilities. 6) Analyzing self-discipline on situational leadership and its impact on employee capabilities. 7) Analyzing the effect of attitude commitment on situational leadership and its impact on employee capabilities. The population in this study were all employees at PT. Rijan Dinamis Selaras (RDS) Pacet Mojokerto numbered 33 people. The sampling method in this writing uses the census technique. Data analysis using SPSS version 20 for validity test with factor analysis, reliability test with Cronbach. Classical assumption test and multiple linear regression analysis, to verify and prove the research hypothesis. From the results of the study, it can be concluded as follows: 1) Self-discipline has no effect on situational leadership 2) Attitude commitment has a significant effect on situational leadership 3) Self-discipline has no effect on employee capabilities 4) Attitude commitment has no effect on employee capabilities 5) Situational leadership significant effect on employee capabilities 6) Self-discipline has an indirect effect on employee capabilities through situational leadership 7) Attitude commitment has an indirect effect on employee capabilities through situational leadership.